12-segment display for the Bengali numerical characters - Pathan, Al-Sakib Khan; Alam, Md. Mahbub; Monowar, Mostafa; Rabbi, Forhad; Ahmed, Sabbir; Khan, Tareq Hasan (Independent University Bangladesh (IUB), 2004)
For representing the Bengali numerical characters the researchers have been working for a long time. In this paper, the idea of 12-segment display is introduced which ensures better outlook than the existing or proposed display systems. A 12-segment display for Bengali Numerical Characters needs 4-bit inputs for representing each digit. Appropriate logic circuits are also designed for that purpose.